Cognitive warfare: a conceptual analysis of the NATO ACT cognitive warfare exploratory concept - Deppe, Christoph; Schaal, Gary S. (Frontiers in Big Data, 2024)
This study evaluates NATO ACT's cognitive warfare concept from a political science perspective, exploring its utility beyond military applications. Despite its growing presence in scholarly discourse, the concept's interdisciplinary nature has hindered a unified definition. By analyzing NATO's framework, developed with input from diverse disciplines and both military and civilian researchers, this paper seeks to assess its applicability to political science. It aims to bridge military and civilian research divides and refine NATO's cognitive warfare approach, offering significant implications for enhancing political science research and fostering integrated scholarly collaboration.